Recommender system for business development using POI - Divya, R.; Angel Latha Mary, S. (International Journal of Engineering and Technology, 2017)
In the technology era, internet access is  unavoidable to find something or to share something with the world. Because of Globalization, the need for   withstanding in the competitive business market is a challenging task. If we are to start a  new business, ideas are needed. It is a tough task to decide where to start a new business with a scope of good profit as well as what type of business to start. If the business is a existing system, then how to increase the profit will be a challenging task.  Unfortunately, no existing system is available for business recommendation. The proposed system is a step to solve this problem. Our paper deals with this challenge.Initially, the user’s interest is obtained to fix a location as well as preferences were obtained for profit maximization. Then, the nearest neighbor is calculated from user’s preferences, checks for available businesses and recommends the business type to the user. In this paper, the step to calculate nearest neighbor for the preferences that the user gives are elaborated.